A comparison between whole mung bean and decorticated mung bean: beneficial effects on the regulation of serum glucose and lipid disorders and the gut microbiota in high-fat diet and streptozotocin-induced prediabetic mice. Issue 6 (9th June 2020) - Hou, Dianzhi; Zhao, Qingyu; Yousaf, Laraib; Chen, Borui; Xue, Yong; Shen, Qun
Abstract : This study aimed to investigate the beneficial effects of whole and decorticated mung beans on the regulation of serum glucose and lipid disorders in HFD/STZ-induced prediabetic mice, and to further explore their gut microbiota modulatory effects. Abstract : The aim of this study is to investigate the beneficial effects of whole mung bean (WMB) and decorticated mung bean (DMB) on the regulation of serum glucose and lipid disorders in high-fat diet (HFD) and streptozotocin (STZ)-induced prediabetic mice, and to further explore their gut microbiota modulatory effects. In the present study, the ability of mung bean-based diets to combat prediabetes-related metabolic disorders was determined by assessing the changes in the physiological, biochemical, and histological parameters, and the gut microbiota composition of prediabetic mice. The supplementation of both WMB and DMB can effectively alleviate HFD and STZ-induced impaired glucose tolerance ( P < 0.05), which was accompanied by improvements in pancreatic β-cell damage and hepatic steatosis. However, only WMB supplementation significantly decreased the fasting blood glucose and fasting serum insulin levels by sensitizing insulin action ( P < 0.05), and reduced the serum lipid profiles and glycosylated serum protein levels ( P < 0.05). Furthermore, high-throughput pyrosequencing of the 16S rRNA gene revealed that WMB and DMB supplementation could prevent HFD and STZ-induced gut microbiota dysbiosis, especially for the enrichment of some benign bacteria, such as Bifidobacterium and Akkermansia, and the reduction of some harmful bacteria ( Staphylococcus and Enterococcus ). Overall, although decortication processing had an impact on the beneficial effects of mung bean, it did not cause the loss of all health benefits.